Neoliberal Urban Governance Spaces, Culture and Discourses in Buenos Aires and Chicago - Sternberg, Carolina (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
XVII, 208 p. 17 illus., 14 illus. in color.